2013
DOI: 10.1121/1.4788996
|View full text |Cite
|
Sign up to set email alerts
|

Plenum window insertion loss in the presence of a line source—A scale model study

Abstract: The acoustical insertion losses of plenum windows installed on a building facade in the presence of a non-parallel line source are studied by using a 1:4 scaled down model in a semi-anechoic chamber in the present investigation. Two types of insertion losses, weighted by the normalized traffic noise spectrum (from the 100 Hz to 5000 Hz one-third octave bands), are defined with different references. The first one is for the case where the orientation of the building facade relative to the line source is fixed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 12 publications
0
21
1
Order By: Relevance
“…which is equivalent to the one-third octave band noise reduction adopted in Tong and Tang [12] as their receiver room is very reverberant such that the sound absorptions in m 2 Sabine are numerically very close to the room constants.…”
Section: Definitions Of Insertion Losses and Acoustical Benefitsmentioning
confidence: 97%
See 1 more Smart Citation
“…which is equivalent to the one-third octave band noise reduction adopted in Tong and Tang [12] as their receiver room is very reverberant such that the sound absorptions in m 2 Sabine are numerically very close to the room constants.…”
Section: Definitions Of Insertion Losses and Acoustical Benefitsmentioning
confidence: 97%
“…Kang and Brocklesby [10] studied the use of thin micro-perforated panels in improving the acoustic protection capacity of the window. Tong and Tang [12] carried out a scale model study on the acoustical performance of the plenum windows. It is found that apart from the window opening size and air gap width, the window's orientation relative to the noise source has great influence on the acoustical protection.…”
Section: Introductionmentioning
confidence: 99%
“…It is now commonly referred to as a ventilation window or plenum window [60,61] (hereinafter referred to as plenum window). This device is a double-walled (usually glass panes) plenum structure, with a staggered air inlet and outlet.…”
Section: Plenum Windows/double-wall Structures With Staggered Air Inlmentioning
confidence: 99%
“…A parametric study on the sound insertion loss of a horizontal type plenum window was carried out by Tong and Tang [61], using 1:4 scale model experiments. The effect of the window orientation, relative to the sound source, θ, was also tested.…”
Section: Plenum Windows/double-wall Structures With Staggered Air Inlmentioning
confidence: 99%
“…This staggered inlet and outlet opening window system, referred as plenum window hereafter, has been attracted many researchers as it can provide high sound insulation while allowing natural ventilation across it. Plenum window proved to be effective on providing acoustical protection to the residential buildings compared to the conventional window system [12,13]. In this paper, full scale laboratory measurements were carried out to investigate the effects of various plenum window configuration parameters to the acoustical performance of this facade device.…”
Section: Introductionmentioning
confidence: 99%